A Single Centre Analysis of Clinical Characteristics and Treatment of Endocrine Pancreatic Tumours. (8th June 2015) - Adil, M. T.; Nagaraja, R.; Varma, V.; Mehta, N.; Kumaran, V.; Nundy, S.
Abstract : Background . Endocrine Pancreatic Tumours (PENs) are rare and can be nonfunctioning or functioning. They carry a good prognosis overall though high grade lesions show a relatively shorter survival. The aim of the current study is to describe a single centre analysis of the clinical characteristics and surgical treatment of PENs. Patients and Methods . This is a cohort analysis of 40 patients of PENs who underwent surgery at Sir Ganga Ram Hospital, New Delhi, India, from 1995 to 2013. Patient particulars, clinical features, surgical interventions, postoperative outcome, and followup were done and reviewed. The study group was divided based on grade (G1, G2, and G3) and functionality (nonfunctioning versus functioning) for comparison. Results . PENs comprised 6.3% of all pancreatic neoplasms (40 of 634). Twenty-eight patients (70%) had nonfunctioning tumours. Eighteen PENs (45%) were carcinomas (G3), all of which were nonfunctioning. 14 (78%) of these were located in the pancreatic head and uncinate process (P = 0.09 ). The high grade (G3) lesions were significantly larger in size than the lower grade (G1 + G2) tumours (7.0 ± 3.5 cms versus 3.1 ± 1.6 cms, P = 0.007 ). Pancreatoduodenectomy was performed in 18 (45%), distal pancreatectomy in 10 (25%), and local resection in 8 (20%) and nonresective procedures were performed in 4 patients (10%). Fourteen patients (35%) had postoperative complications. All G3 grade tumours which were resected had positive lymph nodes (100%) and 10 had angioinvasion (71%). Eight neoplasms (20%) were cystic, all being grade G3 carcinomas, while the rest were solid. The overall disease related mortality attributable to PEN was 14.3% (4 of 28) and for malignant PENs was 33.3% (4 of 12) after a mean follow-up period of 49.6 months (range: 2–137 months). Conclusion . Majority of PENs are nonfunctioning. They are more likely malignant if they are nonfunctioning and large in size, show cystic appearance, and are situated in the pancreatic head. Early surgery leads to good long term survival with acceptable postoperative morbidity.